Geology and the control of lithology to vegetation change by using remove sensing at Takalar regency , South Sulawesi Indonesia - Puteri Najihah Mohamad Zamzani (2018)
Administratively, the study area is located at Takalar Regency, South Sulawesi Indonesia. Astronomically, the study area of geological mapping is located at longitude 119 28’ 30” to ll9 32’ 00"’ E and latitude of5 30’ Z0” to 5 32’ 30” N which covers of 25 km2, while, the study area of remote sensing is located at longitude of l l9 24’ 00” to 119 32’ 00” E and latitude of5 27’ 05” to 5 32’ 40” N, covers of 261 km2. Purpose of the geology study is to determine the characterististic of Camba Formation, Tonasa Formation and Batuan Gunungapi Baturape through physical characteristic and thin section analysis. Limestone, Volcanic Breccia, and Tuff are dominant rocks found in the study area. The age of these rocks were from Late Eocene to Late Pliocene. However, the rocks on Camba Formation lies unconformity on the Tonasa Formation regarding to the Law of Superposition. Basically, the depositional environment of the study area is assumed in deep to shallow marine, lagoon and tidal ﬂat. Fossil such as foraminifera, pelloid and fecal pellets are also found as evidence to the depositional environment. The purpose of speciﬁcation study is to determine the relationship between vegetation index algorithms using remote sensing technique and determine a location of vegetation change based on lithology using satellite imagery to produce a thematic map. For the speciﬁcation study, the change ofvegetation is related to the distribution oflithology. The vegetation change is seen in a large scale of area by using remote sensing based on analysis of vegetation indices such as NDVI, EV] and SAVI. Overall, the study is concern on the relationship between geology and remote sensing aspect which covers of lithology characteristics, mineral distribution, geomorphologic classiﬁcation, stratigraphy and the vegetation change on a different kind of rock